“Siempre tienen a los pobres entre ustedes” (Jn 12, 8): la opción por los pobres: límites y desafíos para hoy (2018)
Regularly, the passage of John 12, 8 is used to justify the presence of the poor in the social context, as if it were a necessary condition, as something inevitable, natural and divine. The Medellín Conference brought forward in the theological and pastoral discussion the reality of poverty as an antievangelical situation. The implications of this challenge marked the impulse to accompany the demands of the social subjects in their aspirations for the political changes in Latin America that would end the conditions of economic and social marginalization, thus expanding the spectrum of their commitment. Today we find a continent that continues to look for ways out of these structural and cultural conditions that do not allow for the much desired change, because we still “have” the poor in our midst, and some do not resign ourselves to accept it as a divine or historical design. It is necessary a rereading that brings us closer to the biblical text with different eyes to better understand the challenge of Jesus today. These are the concerns that we intend to discuss in this paper, fifty years after the Medellin call to listen to the cry of the poor.